PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DIMODERASI SUPERVISI KEPALA SEKOLAH (Studi Pada Guru - Guru PNS SD Di Upt Disdikpora Kecamatan Gringsing Kabupaten Batang) - Sri Winarti, 12.5202.0127; Basiya, R. (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analize the influence of commitment and competence on teacher performanceÂ  moderated by headmaster supervision. Testing instrument using validity and reliability,normality test,asumption test using heteroskedastisitas, are testing a model using the coefficient of determination and the F test (Goodness of Fit). The results of hypotheses testing obtained the results that competence of teacher positively and significance effect of the teacher performance, Â organizational commitment unsignifiance effect of the teacher performance, headmaster supervision positively and significance effect of the teacher performance, headmaster supervision weakness then the influence competence on teacher performance and headmaster supervision donâtÂ  influence on commitment withÂ  teacher performance Keywords: competence, commitment, supervision, teacher performance.